2019
DOI: 10.5114/ada.2018.79940
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors therapy in older patients (≥ 70 years) with metastatic melanoma: a multicentre study

Abstract: IntroductionThe use of immunotherapy in older patients remains challenging due to very few data on the efficacy and safety of treatment in this group.AimTo analyse the efficacy and safety of immunotherapy with checkpoint inhibitors in older patients (≥ 70 years) with metastatic melanoma.Material and methodsIn the Maria Skłodowska-Curie Institute – Oncology Centre, between 2011 and 2017, 318 non-resectable or metastatic melanoma patients were treated with immune checkpoint inhibitors: anti-CTLA-4 or/and anti-PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Various immune checkpoint inhibitor anticancer drugs targeting the PD-1/PD-L1 checkpoint have been approved for clinical use in some cancers, including metastatic melanoma, non-small-cell lung carcinoma (NSCLC), renal cell carcinoma, and UC. Additionally, there are ongoing clinical trials in other solid tumors and hematological cancers [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Various immune checkpoint inhibitor anticancer drugs targeting the PD-1/PD-L1 checkpoint have been approved for clinical use in some cancers, including metastatic melanoma, non-small-cell lung carcinoma (NSCLC), renal cell carcinoma, and UC. Additionally, there are ongoing clinical trials in other solid tumors and hematological cancers [15,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Also our analyses confirmed that the survival and toxicity profile in the older patients (≥ 70 years) treated with immune checkpoint inhibitors including nivolumab are similar to younger patients (< 70 years). In fact even the presence of co-morbidities may not associated with an increased risk of immunotherapy toxicity (p = 0.790) [67]. Recently published data are also indicating that patients age ≥70 with indirect frailty markers such as having fallen in the prior six months, ECOG PS ≥2 or Charlson comorbidity scores ≥11 experience similar rates of immunotherapy toxicity [68].…”
Section: Safety Of Nivolumab In Challenging Subgroups Of Patientsmentioning
confidence: 99%
“…For example, Sun et al revealed that there was no significant difference in the OS of patients with NSCLC using PD-1/PD-L1 inhibitors between the young group (< 65 years old) and the old group (≥65 years old) (12). At the cutoff point of 70 years old, the PFS and OS of patients treated with ICIs in the melanoma, NSCLC and pan-cancer datasets were similar (13)(14)(15). Another analysis of renal cell carcinoma (RCC) and urothelial carcinoma (UC) as a whole or in subgroups showed that older patients over 75 years old had disease control rates (DCRs) comparable to those of younger patients treated with ICIs (16).…”
Section: Introductionmentioning
confidence: 99%